Heat dissipation enhancement method for finned heat sink for AGV motor driver's IGBT module - LIU Xuan; ZHANG Mingchao; LIU Chengwen; ZHOU Chuanan; LV Xiaoling (高技术通讯（英文版）, 2024)
With the widespread use of high-power and highly integrated insulated gate bipolar transistor(IGBT),their cooling methods have become challenging.This paper proposes a liquid cooling scheme for heavy-duty automated guided vehicle(AGV)motor driver in port environment,and im-proves heat dissipation by analyzing and optimizing the core component of finned heat sink.Firstly,the temperature distribution of the initial scheme is studied by using Fluent software,and the heat transfer characteristics of the finned heat sink are obtained through numerical analysis.Secondly,an orthogonal test is designed and combined with the response surface methodology to optimize the structural parameters of the finned heat sink,resulting in a 14.57%increase in the heat dissipation effect.Finally,the effectiveness of heat dissipation enhancement is verified.This work provides val-uable insights into improving the heat dissipation of IGBT modules and heat sinks,and provides guidance for their future applications.